Climatic and environmental changes during the late Holocene at Harier area, North of Basrah Governorate, Southern Iraq - Klakhan, Saba Q.; Muhammad, Abbas H.; Al-Jubouri, Buthaynah S. (Mesopotamian Journal of Marine Sciences, 2020)
The present article includes a Palynomorphs analysis of the recent sediments of Harier area in the north of Basrah Governorate. Thirty six samples were analyzed; Pollen diagrams were drown depending on the percentage of some pollen, spores that indicate environmental and climatic changes. Five pollen zones were recorded which represent the climate of Late Holocene period. This study revealed new results of environmental and climatic changes during the late Holocene period in the marshes areas of southern Iraq, especially the study area. About 30 species and 14 Genera of pollen, 6 species of spores, 8 forms of fungi and Dinoflagellate were recorded.